2018
DOI: 10.3389/fpsyt.2018.00522
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Anterior Thalamic Radiation Structure in Bipolar Disorder: A Diffusion Tensor Tractography Study

Abstract: Disrupted white matter (WM) integrity in the anterior thalamic radiation (ATR) has been identified in individuals with bipolar disorder (BD). We explored whether structural WM aberration in the ATR could be visually evaluated by diffusion tensor tractography (DTT). The study comprised 114 participants, including 57 patients with BD and 57 healthy controls (HCs). A poorly visualized ATR reflects an abnormal WM structure. We defined a poorly visualized ATR as one in which at least one ATR fiber bundle failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
(22 reference statements)
4
27
1
1
Order By: Relevance
“…In the present study, the MCI-PA group exhibited significantly lower microstructural integrity of the anterior thalamic radiation than the MCI-NA group did. The left anterior thalamic radiation is a white matter bundle that connects the anterior and dorsomedial thalamic nuclei to the prefrontal cortex, mainly the orbitofrontal and dorsolateral prefrontal cortex, and it is involved in executive function and planning complex behaviors ( Niida et al, 2018 ). Thalamus activation has been linked to dispositional mindfulness ( Gartenschlager et al, 2017 , Wang et al, 2014 ), and lesions on the anterior thalamic radiation have been identified to be associated with apathetic manifestations in MCI ( Torso et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the MCI-PA group exhibited significantly lower microstructural integrity of the anterior thalamic radiation than the MCI-NA group did. The left anterior thalamic radiation is a white matter bundle that connects the anterior and dorsomedial thalamic nuclei to the prefrontal cortex, mainly the orbitofrontal and dorsolateral prefrontal cortex, and it is involved in executive function and planning complex behaviors ( Niida et al, 2018 ). Thalamus activation has been linked to dispositional mindfulness ( Gartenschlager et al, 2017 , Wang et al, 2014 ), and lesions on the anterior thalamic radiation have been identified to be associated with apathetic manifestations in MCI ( Torso et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior thalamic radiation is known for its role in emotional processes and low FA in this structure is related to sadness (Coenen et al, 2012 ; Jia et al, 2014 ; Niida et al, 2018 ). Anterior parts of the cingulum , terminating in the frontal lobe, are also involved in attention and executive function (Takahashi et al, 2010 ; Chiang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar to a key feature of CO-OP (Missiuna et al, 2001), emotions could be regulated when guided by a significant adult (e.g., therapist or parents; Williams et al, 2020). The anterior thalamic radiation is known for its role in emotional processes and low FA in this structure is related to sadness (Coenen et al, 2012;Jia et al, 2014;Niida et al, 2018). Anterior parts of the cingulum, terminating in the frontal lobe, are also involved in attention and executive function (Takahashi et al, 2010;Chiang et al, 2016).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Our study showed the presence of bilateral ATR damage in MDD. Previous studies showed that the FA decrease of ATR was also found in bipolar disorder (BD), indicating that ATR plays an important role in the onset of affective disorders [ 14 ], though this may be related to the different participants. The FA reduction in LCST has been widely reported in previous studies on BD, which is similar to the findings located in MDD in our study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%